Melanin-concentrating hormone regulates the hypercapnic chemoreflex by acting in the lateral hypothalamic area - Rodrigues, Laísa T. C. [UNESP]; Patrone, Luis Gustavo A. [UNESP]; Gargaglioni, Luciane H. [UNESP]; Dias, Mirela B. [UNESP] (Wiley, 2022)
New Findings: What is the central question of this study? Melanin-concentrating hormone (MCH) suppresses the hypercapnic chemoreflex: what is the mechanism by which this effect is produced? What is the main finding and its importance? MCH acting in the lateral hypothalamic area but not in the locus coeruleus in rats, in the light period, attenuates the hypercapnic chemoreflex. The data provide new insight into the role of MCH in the modulation of the hypercapnic ventilatory response. Abstract: Melanin-concentrating hormone (MCH) is a hypothalamic neuropeptide involved in a broad range of homeostatic functions including regulation of the hypercapnic chemoreflex. We evaluated whether MCH modulates the hypercapnic ventilatory response by acting in the lateral hypothalamic area (LHA) and/or in the locus coeruleus (LC). Here, we measured pulmonary ventilation ((Formula presented.)), body temperature, electroencephalogram (EEG) and electromyogram (EMG) of unanaesthetized adult male Wistar rats before and after microinjection of MCH (0.4 mM) or MCH receptor 1 (MCH1-R) antagonist (SNAP-94847; 63 mM) into the LHA and LC, in room air and 7% CO2 conditions during wakefulness and sleep in the dark and light periods. MCH intra-LHA caused a decreased CO2 ventilatory response during wakefulness and sleep in the light period, while SNAP-94847 intra-LHA increased this response, during wakefulness in the light period. In the LC, MCH or the MCH1-R antagonist caused no change in the hypercapnic ventilatory response. Our results suggest that MCH, in the LHA, exerts an inhibitory modulation of the hypercapnic ventilatory response during the light-inactive period in rats.
Keywords: central chemoreception; hypercapnia; MCH